Model of Creating Sustainable Food Security of Households in NongMek Sub-District, Nachueak District, MahaSarakham Province - Pawala, Tunyachanok; soonthornchai, Assoc. Prof. Dr. Phanita (Journal for Developing the Social and Community, 2018)
This study is mixed methods research by using participatory rural appraisal (PRA) research, the sample was selected with purposive sampling living in Nong Mek SubDistrict, Nachueak District, MahaSarakham consisted of 400 households, to study household food security and select target groups from community leaders, folk philosopher 50 villagers use forest and water. The methods are group meeting and brainstorming, to study the model of food security of households and communities from the natural resource base. The results are as follows: analyze the risk factors, vulnerability and potential of the food security community. The community is self-reliant on food from three food sources consisted of 1) in the home, households can produce their own food using community ingredients.2) Food source from water and 3) food source from the forest. The food security of the household has three main components: 1) the ability to find food. (With adequate food), 2) Access to the food of the household (Sufficient resources for all households to find food) and 3) the use of food (With knowledge and how to take advantage of food, including access to sanitation and water resources) the conserve and restore sufficient food sources. People in the community have a common practice it helps to maintain the food source of the community. Do not dispose of wastewater. Not deforestation eats vegetables. No fishing in the spawning season. Help keep the natural resources from deteriorating. The lives sufficiently, cultivate a sense of reforestation, encourage people in the community to reduce the use of chemicals, address ecological sustainability and safety in the future, such as reducing the use of chemicals. Keep your own produce sufficient. The seeds are planted in the next season and tradition to generation generations and to share or exchange food in the community.